Teflon glass fabric adhesive tape and preparation method thereof

By combining maleic anhydride grafted polyethylene modified glass fiber with nano-silica modified epoxy resin, high-performance Teflon glass fiber cloth tape was prepared, which solved the reduction of flexibility of existing tapes in high temperature environments. and cost issues, achieving wider applications and higher performance.

CN119432237APending Publication Date: 2025-02-14PASINDIMU TECH (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638518.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-17
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing Teflon fiberglass fiberglass tape has reduced flexibility in high temperature environments, and the coating is not firmly combined with the fiberglass fiberglass, which is relatively high, which limits its application in cost-sensitive fields.

Method used

Maleic anhydride grafted polyethylene modified glass fiber and composited with nano-silica modified epoxy resin to prepare a strong composite glass fiber cloth through a woven process, combined with Teflon coating to form high performance adhesive tape.

Benefits of technology

It improves the high temperature resistance and flexibility of the tape, enhances the mechanical properties and chemical stability of the material, and reduces production costs and expands its application in more fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137794370000111
    Figure BDA0005137794370000111
  • Figure BDA0005137794370000121
    Figure BDA0005137794370000121
Patent Text Reader

Abstract

The invention discloses a Teflon glass fabric adhesive tape and a preparation method thereof, and relates to the field of adhesive tapes. The preparation method comprises the following steps: firstly, preparing glass fiber cloth from maleic anhydride grafted polyethylene modified glass fibers, then compounding nano silicon dioxide modified epoxy resin with the glass fiber cloth, and then coating a Teflon layer to form the adhesive tape. When the composite glass fiber cloth is subjected to external force, stress can be effectively transmitted to the glass fibers from the epoxy resin matrix, the nano-silica modified epoxy resin can better bear and transmit stress due to the high strength and high modulus characteristics of the nano-silica modified epoxy resin, and the glass fibers bear main loads by means of the excellent mechanical property of the glass fibers, so that the composite glass fiber cloth is more excellent in mechanical property. The good dispersity and interface bonding force of the maleic anhydride grafted polypropylene modified glass fibers ensure the effective reinforcing effect of the glass fibers in an epoxy resin matrix, and all the components have a synergistic effect, so that the overall mechanical property of the composite glass fabric is improved. The prepared Teflon glass fabric adhesive tape is stable in chemical property and excellent in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive tapes, in particular to a Teflon glass fiber cloth adhesive tape and a preparation method thereof. Background Art

[0002] Teflon fiberglass cloth tape is a high-performance material made of glass fiber cloth as the base material and coated with Teflon. It plays a key role in many fields of industry and daily life. In the industrial field, it is used for insulation and fixation of electronic components in the electronics industry, for equipment sealing and protection in the chemical industry, for engine compartment wiring harness wrapping and high-temperature component insulation in the automotive manufacturing field; for food processing equipment conveyor belts in the food processing field, and for aircraft engine insulation, sealing and protection in the aerospace field. Its development originated from the discovery of Teflon materials. With the development of industry, in order to solve the problems of insufficient strength of Teflon single material, it was combined with glass fiber cloth. However, the early process had problems such as the coating and glass fiber cloth were not firmly combined and the performance was unstable. After the pretreatment of glass fiber, optimization of Teflon emulsion and coating process improvement, the performance was greatly improved and the application field was continuously expanded.

[0003] However, Teflon fiberglass cloth tapes are currently facing some problems. There is a risk of delamination between the coating and the fiberglass cloth, mainly because Teflon has stable chemical properties and is difficult to bond, and traditional processes are difficult to ensure long-term stable bonding; in high-temperature environments, improving high-temperature resistance often leads to reduced flexibility; at the same time, high-performance materials and complex processes make the cost high, limiting its application in cost-sensitive fields. The use of resin composite fiberglass cloth to prepare tapes has many benefits. The resin can fill the gaps in the glass fiber and interact with the glass fiber and Teflon coating. For example, epoxy resin can enhance the connection, solve the problem of weak bonding, and improve stability; by selecting the right resin, you can balance flexibility and high-temperature resistance. For example, some thermoplastic resins can keep the tape flexible at high temperatures and broaden the application temperature range; it is also possible to optimize the resin formula to reduce costs, improve production processes and improve efficiency while ensuring performance, and promote the promotion and application of tapes in more fields. Summary of the invention

[0004] The object of the present invention is to provide a Teflon glass fiber cloth tape and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing Teflon glass fiber cloth tape, characterized in that it comprises the following preparation steps:

[0006] (1) polyethylene, maleic anhydride and initiator are weighed in proportion, mixed evenly and added into a melt extruder, parameters are adjusted, an antioxidant is added, extrusion granulation is performed, and drying is performed to obtain maleic anhydride grafted polyethylene;

[0007] (2) taking glass fiber, soaking it in an organic solvent, then rinsing it with deionized water, and drying it in an oven to constant weight;

[0008] (3) adding the maleic anhydride grafted polyethylene to the solvent in a certain proportion, stirring, and dispersing uniformly to prepare a maleic anhydride grafted polyethylene solution;

[0009] (4) dipping the pretreated glass fiber in the maleic anhydride grafted polyethylene solution, stirring, and pulling it out at a certain speed using a traction device after the dipping is complete, drying it at room temperature, and drying and curing it in an oven;

[0010] (5) using a weaving process to weave the modified glass fiber into maleic anhydride grafted polyethylene modified glass fiber cloth;

[0011] (6) heating the epoxy resin, adding nano-silicon dioxide and a curing agent under stirring, and vacuum degassing to obtain a nano-silicon dioxide modified epoxy resin;

[0012] (7) cutting the maleic anhydride grafted polyethylene modified glass fiber cloth obtained in step (5) into a suitable size, wiping the surface with ethanol, and drying in an oven;

[0013] (8) dipping the pretreated glass fiber cloth in nano-silicon dioxide modified epoxy resin, and after dipping, controlling the resin content on the glass fiber cloth by an extrusion roller or a doctor blade device to obtain a nano-silicon dioxide modified epoxy resin composite modified glass fiber cloth;

[0014] (9) taking a polytetrafluoroethylene dispersion, adding a defoamer and a curing agent with stirring, and stirring and mixing to obtain a Teflon emulsion;

[0015] (10) Slowly impregnating the nano-silicon dioxide modified epoxy resin composite modified glass fiber cloth into Teflon emulsion, and curing and drying after the impregnation is complete to obtain Teflon glass fiber cloth tape;

[0016] The nano silicon dioxide is prepared by the following steps:

[0017] (i) Weigh ethyl orthosilicate and ethanol in a container in a mass ratio, stir, add deionized water to dissolve, keep the temperature in a water bath, add a catalyst and an organic silane coupling agent, continue to stir and mix evenly, condense and reflux to obtain a uniform nano-silica sol, and dry and sinter to obtain nano-silica.

[0018] Furthermore, the polyethylene in step (1) is low-density polyethylene; the mass ratio of the polyethylene to maleic anhydride is 15-20:1; the initiator is dicumyl peroxide; and the antioxidant is lauryl thiodipropionate.

[0019] Furthermore, the solvent in step (3) is toluene; and the mass fraction of the prepared maleic anhydride grafted polyethylene solution is 10-20%.

[0020] Furthermore, the pulling rate of step (4) is 0.5-2 m / min; the curing time is 1-5 h; the oven heating rate is 2-5°C / min, first slowly heating to 80-100°C, maintaining for 0.5-1.5 h, and then continuing to heat to 120-150°C, maintaining for 0.5-3 h.

[0021] Furthermore, in step (5), the warp density is 10 to 30 yarns / cm, and the weft density is 8 to 25 yarns / cm; the warp tension is 5 to 15 cN, and the weft tension is 3 to 10 cN; and the loom speed is 100 to 500 rpm.

[0022] Furthermore, the epoxy resin in step (6) is bisphenol A epoxy resin; and the curing agent is diethylenetriamine.

[0023] Furthermore, the resin content in step (8) is 30-60%; the impregnation time is 10-60 seconds, and the impregnation speed is 0.1-0.5 m / min.

[0024] Furthermore, the solid content of the polytetrafluoroethylene dispersion in step (9) is 50-60%; the defoaming agent is a polyether-modified silicone oil defoaming agent; and the curing agent is hexamethylenediamine.

[0025] Furthermore, a Teflon glass fiber cloth tape is provided, characterized in that the tape is prepared by the method.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] The invention uses maleic anhydride grafted polyethylene to modify glass fiber. Maleic anhydride molecules contain anhydride groups with high activity. Under appropriate conditions, these anhydride groups can react chemically with active groups such as hydroxyl groups on the surface of glass fiber to form chemical bonds. This chemical bonding enables polyethylene chains to be firmly grafted on the surface of glass fiber, thereby realizing the modification of glass fiber. The grafted polyethylene chains can also interact with glass fiber by means of physical entanglement and the like, further enhancing the bonding force between the two and improving the mechanical properties of the material. The grafted polyethylene chains can protect glass fiber from being corroded by chemical substances and synergistically act with maleic anhydride groups to improve the chemical resistance of formed glass fiber cloth. Meanwhile, the polyethylene structure is similar to the matrix resin and can be better integrated with the matrix resin, thereby reducing interface defects and improving the comprehensive performance of the resin composite glass fiber cloth material.

[0028] The present invention uses nano-silicon dioxide modified epoxy resin composite modified glass fiber cloth. Nano-silicon dioxide particles are used as inorganic fillers and can be evenly dispersed in epoxy resin to form an inorganic-organic hybrid structure. This structure enables the composite material to disperse stress more effectively when subjected to external force, thereby improving the overall tensile strength, impact strength and elongation at break of the material; the interaction between the nano-silicon dioxide and the resin matrix can absorb part of the heat, thereby delaying the thermal degradation process of the composite material and improving the chemical stability.

[0029] The polypropylene chain on the surface of the modified glass fiber can form good compatibility with epoxy resin, which is conducive to the infiltration and adhesion of epoxy resin on the surface of glass fiber, making the interface between the two more closely bonded. At the same time, the uniform dispersion of nano-silicon dioxide in epoxy resin also helps to increase the contact area and interaction between epoxy resin and glass fiber, thereby forming a strong and tough interface layer. Due to the excellent combination of each component, when the composite glass fiber cloth is subjected to external force, the stress can be effectively transferred from the epoxy resin matrix to the glass fiber. The high strength and high modulus characteristics of nano-silicon dioxide modified epoxy resin enable it to better bear and transfer stress, while the glass fiber bears the main load with its excellent mechanical properties. The good dispersibility and interfacial bonding force of maleic anhydride grafted polypropylene modified glass fiber ensure the effective reinforcement of glass fiber in the epoxy resin matrix. The synergistic effect of each component enables the stress to be evenly distributed throughout the composite material, avoiding the occurrence of stress concentration, thereby improving the overall mechanical properties of the composite glass fiber cloth. Furthermore, epoxy resin itself has a bonding effect. When epoxy resin is combined with glass fiber, it fills the gaps between the glass fibers, bonding the glass fibers into a whole, enhancing the structural strength of the glass fiber cloth. In addition, when it is subsequently combined with the Teflon coating, the presence of epoxy resin also helps the adhesion between the Teflon coating and the glass fiber cloth. Especially during the high-temperature curing process, some chemical bonding or physical adsorption will be formed between the epoxy resin and the glass fiber and between the epoxy resin and the Teflon coating, thereby improving the overall bonding strength. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the Teflon glass fiber cloth tape prepared in the following examples are as follows:

[0032] Peel strength: GB / T 2792-2014

[0033] Adhesion test: GB / T 4851-2014

[0034] Example 1

[0035] (1) 100 parts of low-density polyethylene, 5 parts of maleic anhydride, and 0.2 parts of dicumyl peroxide were weighed in proportion, mixed evenly, and added to a melt extruder, the temperature was adjusted to 225° C., and after reacting for 1 hour, 0.3 parts of lauryl thiodipropionate as an antioxidant was added. After the reaction was complete, the mixture was extruded into granules, and dried to obtain maleic anhydride grafted polyethylene;

[0036] (2) Take glass fiber, soak it in ethanol, then rinse it with deionized water, and dry it in an oven at 110°C to constant weight;

[0037] (3) adding the maleic anhydride grafted polyethylene into toluene to dissolve, stir, and evenly disperse to prepare a maleic anhydride grafted polyethylene solution with a mass fraction of 15%;

[0038] (4) dipping the pretreated glass fiber in the maleic anhydride grafted polyethylene solution, stirring, and pulling out at a rate of 1 m / min using a traction device after complete dipping, drying at room temperature, drying in an oven, first heating to 90° C., maintaining for 1 h, then heating to 135° C., maintaining for 2 h, with a heating rate of 3° C. / min, and curing for 3 h to obtain maleic anhydride grafted polyethylene modified glass fiber;

[0039] (5) placing 1000 parts of maleic anhydride grafted polyethylene modified glass fiber into a weaving machine, adjusting the parameters, the warp density is 20 strands / cm, the weft density is 15 strands / cm, the warp tension is 10 cN, the weft tension is 6 cN, and the loom speed is 300 rpm, to obtain maleic anhydride grafted polyethylene modified glass fiber cloth;

[0040] (6) Weigh 100 parts of ethyl orthosilicate and 200 parts of ethanol in a container, stir, add deionized water to dissolve, keep the temperature in a water bath at 70° C., add 1 part of 0.1M hydrochloric acid as a catalyst and 3 parts of an organic silane coupling agent KH-570, continue to stir and mix evenly, condense and reflux for 3 hours to obtain a uniform nano-silica sol, dry at 100° C. for 1 hour, and sinter at 750° C. for 3 hours to obtain nano-silica;

[0041] (7) heating 100 parts of bisphenol A epoxy resin to 50° C. to melt, adding 10 parts of nano-silicon dioxide under stirring, and after the reaction is complete, adding 3 parts of diethylenetriamine, and vacuum degassing to obtain nano-silicon dioxide modified epoxy resin;

[0042] (8) Go to step (5) to obtain maleic anhydride grafted polyethylene modified glass fiber cloth, cut it to a thickness of 0.3 mm and a width of 2 m, wipe the surface with ethanol, and dry it in an oven at 100° C. for 2 h;

[0043] (9) dipping the pretreated glass fiber cloth in nano-silica modified epoxy resin at a dipping speed of 0.3 m / min, taking it out after dipping for 45 seconds, and then controlling the resin content on the glass fiber cloth to 45% by a scraping device to obtain a nano-silica modified epoxy resin composite modified glass fiber cloth;

[0044] (10) Take 100 parts of a polytetrafluoroethylene dispersion with a solid content of 55%, add 5 parts of polyether ester modified silicone oil and 2 parts of hexamethylene diamine with stirring, and stir and mix to obtain a Teflon emulsion;

[0045] (11) The nano-silica modified epoxy resin composite modified glass fiber cloth was slowly impregnated into the Teflon emulsion for 30 seconds at a speed of 0.2 m / min. After the impregnation was complete, the glass fiber cloth was cured and dried at 100° C. to obtain a Teflon glass fiber cloth tape.

[0046] Example 2

[0047] (1) 120 parts of low-density polyethylene, 8 parts of maleic anhydride, and 0.3 parts of dicumyl peroxide were weighed in proportion, mixed evenly, and added to a melt extruder, the temperature was adjusted to 250° C., and after reacting for 1.5 hours, 0.5 parts of lauryl thiodipropionate, an antioxidant, was added. After the reaction was complete, the mixture was extruded into granules, and dried to obtain maleic anhydride grafted polyethylene;

[0048] (2) Take glass fiber, soak it in ethanol, then rinse it with deionized water, and dry it in an oven at 120°C to constant weight;

[0049] (3) adding the maleic anhydride grafted polyethylene into toluene to dissolve, stir, and evenly disperse to prepare a maleic anhydride grafted polyethylene solution with a mass fraction of 20%;

[0050] (4) Immersing the pretreated glass fiber in the maleic anhydride grafted polyethylene solution, stirring, and pulling it out at a rate of 2 m / min using a traction device after the impregnation is complete, drying at room temperature, drying in an oven, first heating to 100° C., maintaining for 1.5 h, then heating to 150° C., maintaining for 3 h, the heating rate is 5° C. / min, and curing treatment is performed for 5 h to obtain maleic anhydride grafted polyethylene modified glass fiber;

[0051] (5) placing 1200 parts of maleic anhydride grafted polyethylene modified glass fiber into a weaving machine, adjusting the parameters, the warp density is 30 strands / cm, the weft density is 25 strands / cm, the warp tension is 15 cN, the weft tension is 10 cN, and the loom speed is 500 rpm, to obtain maleic anhydride grafted polyethylene modified glass fiber cloth;

[0052] (6) Weigh 120 parts of ethyl orthosilicate and 220 parts of ethanol into a container, stir, add deionized water to dissolve, keep the water bath at 70°C, add 2 parts of 0.1M hydrochloric acid as a catalyst and 5 parts of an organic silane coupling agent KH-570, continue to stir and mix evenly, condense and reflux for 3 hours to obtain a uniform nano-silica sol, dry at 120°C for 2 hours, and sinter at 850°C for 4 hours to obtain nano-silica;

[0053] (7) heating 120 parts of bisphenol A epoxy resin to 30° C. to melt, adding 15 parts of nano-silicon dioxide under stirring, and after the reaction is complete, adding 5 parts of diethylenetriamine, and vacuum degassing to obtain nano-silicon dioxide modified epoxy resin;

[0054] (8) Go to step (5) to obtain maleic anhydride grafted polyethylene modified glass fiber cloth, cut it to a thickness of 0.5 mm and a width of 3 m, wipe the surface with ethanol, and dry it in an oven at 120° C. for 3 h;

[0055] (9) dipping the pretreated glass fiber cloth in nano-silica modified epoxy resin at a dipping speed of 0.5 m / min, taking it out after dipping for 60 seconds, and then controlling the resin content on the glass fiber cloth to 60% by a scraping device to obtain a nano-silica modified epoxy resin composite modified glass fiber cloth;

[0056] (10) Take 120 parts of polytetrafluoroethylene dispersion emulsion with a solid content of 60%, add 8 parts of polyether ester modified silicone oil and 3 parts of hexamethylene diamine with stirring, and stir and mix to obtain Teflon emulsion;

[0057] (11) The nano-silica modified epoxy resin composite modified glass fiber cloth was slowly impregnated into the Teflon emulsion for 45 seconds at a speed of 0.3 m / min. After the impregnation was complete, the mixture was cured and dried at 120° C. to obtain a Teflon glass fiber cloth tape.

[0058] Example 3

[0059] (1) 80 parts of low-density polyethylene, 3 parts of maleic anhydride, and 0.1 parts of dicumyl peroxide are weighed in proportion, mixed evenly, and added into a melt extruder, the temperature is adjusted to 200° C., after reacting for 0.5, 0.. parts of lauryl thiodipropionate as an antioxidant is added, the reaction is complete, extrusion granulation is performed, and drying is performed to obtain maleic anhydride grafted polyethylene;

[0060] (2) Take glass fiber, soak it in ethanol, then rinse it with deionized water, and dry it in an oven at 100°C to constant weight;

[0061] (3) adding the maleic anhydride grafted polyethylene into toluene to dissolve, stir, and evenly disperse to prepare a maleic anhydride grafted polyethylene solution with a mass fraction of 10%;

[0062] (4) Immersing the pretreated glass fiber in the maleic anhydride grafted polyethylene solution, stirring, and pulling it out at a rate of 0.5 m / min using a traction device after the impregnation is complete, drying at room temperature, drying in an oven, first heating to 80° C., maintaining for 0.5 h, then heating to 120° C., maintaining for 0.5 h, the heating rate is 2° C. / min, and curing treatment is performed for 1 h to obtain maleic anhydride grafted polyethylene modified glass fiber;

[0063] (5) placing 800 parts of maleic anhydride grafted polyethylene modified glass fiber into a weaving machine, adjusting the parameters, the warp density is 10 strands / cm, the weft density is 8 strands / cm, the warp tension is 5 cN, the weft tension is 3 cN, and the loom speed is 100 rpm, to obtain maleic anhydride grafted polyethylene modified glass fiber cloth;

[0064] (6) Weigh 90 parts of ethyl orthosilicate and 180 parts of ethanol into a container, stir, add deionized water to dissolve, keep the water bath at 65°C, add 1 part of 0.1M hydrochloric acid as a catalyst and 2 parts of an organic silane coupling agent KH-570, continue to stir and mix evenly, condense and reflux for 2 hours to obtain a uniform nano-silica sol, dry at 90°C for 1 hour, and sinter at 650°C for 2 hours to obtain nano-silica;

[0065] (7) heating 80 parts of bisphenol A epoxy resin to 400° C. to melt, adding 5 parts of nano-silicon dioxide under stirring, and after the reaction is complete, adding 1 part of diethylenetriamine, and vacuum degassing to obtain nano-silicon dioxide modified epoxy resin;

[0066] (8) Go to step (5) to obtain maleic anhydride grafted polyethylene modified glass fiber cloth, cut it to a thickness of 0.1 mm and a width of 1 m, wipe the surface with ethanol, and dry it in an oven at 80° C. for 1 h;

[0067] (9) dipping the pretreated glass fiber cloth in nano-silica modified epoxy resin at a dipping speed of 0.1 m / min, taking it out after dipping for 30 seconds, and then controlling the resin content on the glass fiber cloth to 30% by a scraping device to obtain a nano-silica modified epoxy resin composite modified glass fiber cloth;

[0068] (10) Take 80 parts of a polytetrafluoroethylene dispersion with a solid content of 50%, add 3 parts of polyether ester modified silicone oil and 1 part of hexamethylene diamine, and stir and mix to obtain a Teflon emulsion;

[0069] (11) Slowly dipping the nano-silica modified epoxy resin composite modified glass fiber cloth into the Teflon emulsion for 15 seconds at a dipping speed of 0.1 m / min, and curing and drying at 80° C. after the dipping is complete to obtain a Teflon glass fiber cloth tape;

[0070] Comparative Example 1

[0071] The difference between Comparative Example 1 and Example 1 is that steps (1) to (4) are deleted, and step (5) is changed to placing 1000 parts of glass fibers into a weaving machine, adjusting the parameters, the warp density is 20 strands / cm, the weft density is 15 strands / cm, the warp tension is 10 cN, the weft tension is 6 cN, and the loom speed is 300 rpm to obtain a glass fiber cloth; the remaining steps are the same as in Example 1.

[0072] Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 1 is that steps (1) and (3) are deleted, and step (4) is changed to immersing the pretreated glass fiber in a γ-aminopropyltriethoxysilane solution and stirring. After the impregnation is complete, the glass fiber is pulled out using a traction device at a rate of 2 m / min, dried at room temperature, and dried in an oven. The temperature is first raised to 100°C and maintained for 1.5 h, and then raised to 150°C and maintained for 3 h. The heating rate is 5°C / min, and the curing treatment is performed for 5 h to obtain a silane coupling agent-modified glass fiber. The remaining steps are the same as Example 1.

[0074] Comparative Example 3

[0075] The difference between Comparative Example 3 and Example 1 is that steps (1) and (3) are deleted, and step (4) is changed to treating the pretreated glass fiber with low-temperature plasma, placing it in the equipment, introducing argon gas, treating with a power of 300 W, a time of 15 min, and a gas flow rate of 50 ml / min; the remaining steps are the same as Example 1.

[0076] Comparative Example 4

[0077] The difference between Comparative Example 4 and Example 1 is that steps (6) and (7) are deleted, and step (9) is changed to (9): the pretreated glass fiber cloth is immersed in epoxy resin at an immersion speed of 0.5 m / min, taken out after immersion for 60 seconds, and then the resin content on the glass fiber cloth is controlled to 60% by a scraping device to obtain a bisphenol A type epoxy resin composite modified glass fiber cloth; the remaining steps are the same as those in Example 1.

[0078] Comparative Example 5

[0079] The difference between Comparative Example 5 and Example 1 is that step (6) is deleted and step (7) is changed to: 120 parts of bisphenol A epoxy resin are heated to 30°C to melt, 15 parts of commercially available nano zinc boride are added under stirring, and after the reaction is complete, 5 parts of diethylenetriamine are added, and vacuum degassing is performed to obtain nano silicon dioxide modified epoxy resin; the remaining steps are the same as those in Example 1.

[0080] Comparative Example 6

[0081] The difference between Comparative Example 6 and Example 1 is that step (6) is deleted and step (7) is changed to: 120 parts of bisphenol A epoxy resin are heated to 30°C to melt, 15 parts of commercially available nano titanium dioxide are added under stirring, and after the reaction is complete, 5 parts of diethylenetriamine are added and vacuum degassing is carried out to obtain nano-silicon dioxide modified epoxy resin; the remaining steps are the same as Example 1.

[0082] Comparative Example 7

[0083] The difference between Comparative Example 7 and Example 1 is that steps (2) to (4) are deleted, and step (5) is changed to placing 1000 parts of glass fibers into a weaving machine, adjusting the parameters, the warp density is 20 strands / cm, the weft density is 15 strands / cm, the warp tension is 10 cN, the weft tension is 6 cN, and the loom speed is 300 rpm to obtain a glass fiber cloth; 3 parts of the maleic anhydride grafted polyethylene obtained in step (1) are added to the nano-silica modified epoxy resin in step (7), and the remaining steps are the same as in Example 1.

[0084] Effect example

[0085] Table 1 below shows the performance analysis results of the Teflon glass fiber cloth tapes of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0086]

[0087]

[0088] From the comparison of the data of the embodiment and the comparative example, it can be found that the present invention uses nano-silicon dioxide modified epoxy resin composite modified glass fiber cloth, and the nano-silicon dioxide particles are used as inorganic fillers, which can be evenly dispersed in the epoxy resin to form an inorganic-organic hybrid structure. This structure enables the composite material to disperse stress more effectively when subjected to external force, thereby improving the overall tensile strength, impact strength and elongation at break of the material; the interaction between the nano-silicon dioxide and the resin matrix can absorb part of the heat, thereby delaying the thermal degradation process of the composite material and improving the chemical stability.

[0089] The polypropylene chain on the surface of the modified glass fiber can form good compatibility with epoxy resin, which is conducive to the infiltration and adhesion of epoxy resin on the surface of glass fiber, making the interface between the two more closely bonded. At the same time, the uniform dispersion of nano-silicon dioxide in epoxy resin also helps to increase the contact area and interaction between epoxy resin and glass fiber, thereby forming a strong and tough interface layer. Due to the excellent combination of each component, when the composite glass fiber cloth is subjected to external force, the stress can be effectively transferred from the epoxy resin matrix to the glass fiber. The high strength and high modulus characteristics of nano-silicon dioxide modified epoxy resin enable it to better bear and transfer stress, while the glass fiber bears the main load with its excellent mechanical properties. The good dispersibility and interfacial bonding force of maleic anhydride grafted polypropylene modified glass fiber ensure the effective reinforcement of glass fiber in the epoxy resin matrix. The synergistic effect of each component enables the stress to be evenly distributed throughout the composite material, avoiding the occurrence of stress concentration, thereby improving the overall mechanical properties of the composite glass fiber cloth. Furthermore, epoxy resin itself has a bonding effect. When epoxy resin is combined with glass fiber, it fills the gaps between the glass fibers, bonding the glass fibers into a whole, enhancing the structural strength of the glass fiber cloth. In addition, when it is subsequently combined with the Teflon coating, the presence of epoxy resin also helps the adhesion between the Teflon coating and the glass fiber cloth. Especially during the high-temperature curing process, some chemical bonding or physical adsorption will be formed between the epoxy resin and the glass fiber and between the epoxy resin and the Teflon coating, thereby improving the overall bonding strength.

[0090] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and no mark in the claims should be regarded as limiting the claims involved.

Claims

1. A method for preparing Teflon glass fiber cloth tape, characterized in that: The method comprises the following preparation steps: (1) polyethylene, maleic anhydride and initiator are weighed in proportion, mixed evenly and added into a melt extruder, parameters are adjusted, an antioxidant is added, extrusion granulation is performed, and drying is performed to obtain maleic anhydride grafted polyethylene; (2) taking glass fiber, soaking it in an organic solvent, then rinsing it with deionized water, and drying it in an oven to constant weight; (3) adding the maleic anhydride grafted polyethylene to the solvent in a certain proportion, stirring, and dispersing uniformly to prepare a maleic anhydride grafted polyethylene solution; (4) dipping the pretreated glass fiber in the maleic anhydride grafted polyethylene solution, stirring, and pulling it out at a certain speed using a traction device after the dipping is complete, drying it at room temperature, and drying and curing it in an oven; (5) using a weaving process to weave the modified glass fiber into maleic anhydride grafted polyethylene modified glass fiber cloth; (6) heating the epoxy resin, adding nano-silicon dioxide and a curing agent under stirring, and vacuum degassing to obtain a nano-silicon dioxide modified epoxy resin; (7) cutting the maleic anhydride grafted polyethylene modified glass fiber cloth obtained in step (5) into a suitable size, wiping the surface with ethanol, and drying in an oven; (8) dipping the pretreated glass fiber cloth in nano-silicon dioxide modified epoxy resin, and after dipping, controlling the resin content on the glass fiber cloth by an extrusion roller or a doctor blade device to obtain a nano-silicon dioxide modified epoxy resin composite modified glass fiber cloth; (9) taking a polytetrafluoroethylene dispersion, adding a defoamer and a curing agent with stirring, and stirring and mixing to obtain a Teflon emulsion; (10) Slowly impregnating the nano-silicon dioxide modified epoxy resin composite modified glass fiber cloth into Teflon emulsion, and after the impregnation is complete, curing and drying to obtain Teflon glass fiber cloth tape; The nano silicon dioxide is prepared by the following steps: (i) Weigh ethyl orthosilicate and ethanol in a container in a mass ratio, stir, add deionized water to dissolve, keep the temperature in a water bath, add a catalyst and an organic silane coupling agent, continue to stir and mix evenly, condense and reflux to obtain a uniform nano-silica sol, and dry and sinter to obtain nano-silica.

2. A Teflon glass fiber cloth tape and a preparation method thereof according to claim 1, characterized in that: The polyethylene in step (1) is low-density polyethylene; the mass ratio of the polyethylene to maleic anhydride is 15-20:1; the initiator is dicumyl peroxide; and the antioxidant is lauryl thiodipropionate.

3. A Teflon glass fiber cloth tape and a preparation method thereof according to claim 1, characterized in that: The solvent in step (3) is toluene; the mass fraction of the prepared maleic anhydride grafted polyethylene solution is 10-20%.

4. A Teflon glass fiber cloth tape and a preparation method thereof according to claim 1, characterized in that: The pulling rate of step (4) is 0.5-2 m / min; the curing time is 1-5 h; the oven heating rate is 2-5°C / min, first slowly heating to 80-100°C, maintaining for 0.5-1.5 h, then continuing to heat to 120-150°C, maintaining for 0.5-3 h.

5. A Teflon glass fiber cloth tape and a preparation method thereof according to claim 1, characterized in that: In the step (5), the warp density is 10 to 30 yarns / cm, and the weft density is 8 to 25 yarns / cm; the warp tension is 5 to 15 cN, and the weft tension is 3 to 10 cN; and the loom speed is 100 to 500 rpm.

6. The method for preparing a Teflon glass fiber cloth tape and a method for preparing the same according to claim 1, characterized in that: The epoxy resin in step (6) is bisphenol A epoxy resin; and the curing agent is diethylenetriamine.

7. The method for preparing a Teflon glass fiber cloth tape and a method for preparing the same according to claim 1, characterized in that: The resin content in step (8) is 30-60%; the impregnation time is 10-60 seconds, and the impregnation speed is 0.1-0.5 m / min.

8. The method for preparing a Teflon glass fiber cloth tape and a method for preparing the same according to claim 1, characterized in that: The solid content of the polytetrafluoroethylene dispersion in step (9) is 50-60%; the defoaming agent is a polyether modified silicone oil defoaming agent; and the curing agent is hexamethylenediamine.

9. A Teflon glass fiber cloth tape, characterized in that: The Teflon glass fiber cloth tape is prepared by the method described in any one of claims 1-8.